Gambaran Preferensi Mahasiswa Tahap Preklinik Fakultas Kedokteran Universitas Lampung Terhadap Berbagai Metode Pengajaran - Atica Ramadhani Putri (Unram Medical Journal, 2022)
Background: Recent literature has compared the use of specific teaching methods with the lecture method. Millennial students tend to prefer team-based learning, and suggest a preference for collaborative and technology-based learning approaches, But according to some literatures, medical students prefer the lecture method which is a passive teaching method. Objective: to find out the description of the pre-clinical stage preference of the Faculty of Medicine, University of Lampung towards various teaching methods. Methods: This research is a descriptive study with a survey method, sampling method is by total sampling. The variable in this study is the preference of preclinical students of the Faculty of Medicine, University of Lampung towards various teaching methods. The data was taken directly using a questionnaire for students in 2016 and 2017. The data will be entered into Microsoft Excel and then converted into tabular form and the mean will be calculated for each variable. Results: From the research, results obtained the highest mean of 4.134 for the CSL method, the second is lectures with a mean of 3.717, after that there is PAL with a mean of 3.481, PBL with a mean of 3.334, practicum with a mean of 3.286, CBL with a mean of 3.218, TBL with a mean of 3.184, and the last plenary with a mean of 2.673. Conclusion Preferences of students to a various teaching methods from the highest mean are CSL, lecture, PAL, PBL, practicum, CBL, TBL, and plenary.